Traumatic Brain Injury - Sadaka, Farid (IntechOpen, 2014)
Traumatic brain injury is a major source of death and severe disability worldwide. This book provides an excellent and detailed overview of the management of patients with traumatic brain injury, in a stepwise approach, from the intensive care unit, through to discharge from the hospital, rehabilitation, recovery and assimilation in family and society. This book also discusses mechanisms of pathophysiology pertaining to traumatic brain injury and provides grounds for future research in traumatic brain injury, especially pertaining to pathophysiology, imaging, neuroprognostication, rehabilitation, recovery, and outcomes.